2015
DOI: 10.1016/j.proeng.2015.07.172
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Finite Element Analysis of Steel Bicycle Frames: The Influence of Tube Selection on Frame Stiffness

Abstract: This paper presents a parametric Finite Element model of road bicycle frames using beam elements with varying tube profiles. A range of existing frame geometries were subject to various in plane and out of plane loading conditions to examine the influence of tube profiles (as published by the Reynolds, Columbus and Tange manufacturers) on the lateral stiffness and vertical compliance of the frames. This was an extension of previous work which characterised the influence of overall frame geometries (tube length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Dewasa ini, terjadi peningkatan dalam ketertarikan pada dunia persepedaan [1]. Ada cukup banyak literatur mengenai kemajuan teknologi sepeda.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Dewasa ini, terjadi peningkatan dalam ketertarikan pada dunia persepedaan [1]. Ada cukup banyak literatur mengenai kemajuan teknologi sepeda.…”
Section: Pendahuluanunclassified
“…Ada cukup banyak literatur mengenai kemajuan teknologi sepeda. Hampir sebagian besar mengacu pada pembahasan mengenai keamanan pada bagian frame atau rangka [1][2][3][4][5][6][7]. Dalam perencanaan rangka sepeda, terdapat beberapa prioritas yang harus dipenuhi, antara lain meminimalkan massa dari rangka, memaksimalkan kekakuan saat terjadi perpindahan beban dari tangan dan kaki untuk bergerak, mengatur ketinggian dari rangka untuk mendapatkan sensasi berkendara yang lembut, dan memaksimalkan kemampuan rangka dalam menahan beban yang tinggi [1].…”
Section: Pendahuluanunclassified
“…To complement the progress made in materials and manufacturing technologies, the use of numerical simulations is also becoming more common amongst bicycle designers to analyse frame behavior and, where possible, assist in designing more lightweight and fit for purpose bicycles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Previous studies have shown how finite element analysis (FEA) can be used to support designers in the selection of individual tubes to tune the stiffness and strength behaviour of frames [1,13,15,17,19]. Furthermore, FEA has recently been used to inform the design of individually customised tubes and components using both traditional manufacturing [1] and additive manufacturing technologies [18].…”
Section: Introductionmentioning
confidence: 99%
“…The frames are subjected to various loads at different locations such as handlebars, pedal/cranks, hubs and seatposts which have been measured by researchers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The use of simulation tools in comparing the performance of framesets under static and dynamic conditions with different materials have been presented [20][21][22][23][24][25][26][27][28]. An insight of large companies producing carbon-fibre frames in terms of design and manufacturing is presented by researchers [29][30][31] but no information regarding optimization is stated.…”
Section: Introductionmentioning
confidence: 99%